Compress natural gas composite tank for vehicles. - Ahmadun, Fakhru'l-Razi; Mohd Salleh, Mohamad Amran; Ahmed Saad, Elsadig Mahdi (2007)

(untitled)
The present invention relates to a reinforced compressed natural gas (CNG) composite tank and a method making the same for direct injection in vehicle systems at high pressure wherein the method of making a reinforced CNG composite tank having a desired tank configuration with a cylindrical protuberance on one end of the tank and bossless dome section on the other end, comprises: (a) layering the middle of the dome section of the back end of the liner with layers of carbon fibers; (b) overlayering the liner with a tow of carbon fibers in epoxy resin by winding process; and (c) heating the composite layer of the composite tank by curing process in a mobile oven. The composite tank provided is constructed from aluminum alloy material based liner reinforced with carbon fiber/ epoxy composite.